Praktyki rodzinne w turystyce. Analiza blogów o podróżowaniu z dziećmi - Grotowska, Stella (Człowiek i Społeczeństwo, 2025)
One widely accessible and popular way of improving people’s quality of life is tourism, and its popularity is growing in Poland. The purpose of the article is to describe and analyze family practices developed while independent travelling with children. The research is preliminary. It consists from the qualitative content analysis of Polish-language family travel blogs. It is assumed that bloggers’ discourse includes typical experiences of leisure time in contemporary society. The study shows that, according to bloggers, the desired model of family life is a nuclear family liberated from the social environment („significant others”, state institutions). Strong bonds within the small, two-generation family are based on the search for experiences, surprises, spontaneity and spending „quality”, educational time together. During the journey the process of primary socialization is successfully completed, children internalize their parents’ passion for travelling. The effects of the study can serve as a basis for further research on the role of leisure activities for bonds between family members and the socialization process.